Ce–Nd Co-substituted nanospinel cobalt ferrites: An investigation of their structural, magnetic, optical, and apoptotic properties. Issue 13 (September 2019) - Almessiere, M.A.; Slimani, Y.; Sertkol, M.; Khan, F.A.; Nawaz, M.; Tombuloglu, H.; Al-Suhaimi, E.A.; Baykal, A.
Abstract: In this study, Nd 3+ and Ce 3+ co-substituted Co ferrite nanoparticles (NPs) were prepared using a sonochemical approach. The simultaneous substitution of Nd 3+ and Ce 3+ into CoFe2 O4 nanoparticles (NPs) affected the structure, magnetic properties, and cation distribution. The structural parameters were investigated and calculated via XRD studies. The nanocrystalline morphology was identified by SEM along with EDX and TEM. The appearance of two vibration bands correlated to the Td and Oh group relevant to the spinel ferrite lattice were confirmed by Fourier-transform infrared spectroscopy (FT-IR). Magnetization analyses were conducted at room temperature (300K; RT) and low (10K) temperatures. Different magnetic parameters including the remanence (Mr ), coercivity (Hc ), saturation magnetization (Ms ), squareness ratio (SQR = Mr /Ms ), and magnetic moment ( n B ) were deduced and discussed. The results demonstrated a superparamagnetic (SPM) nature in the x = 0.00 sample at RT. However, the other samples (0.03 ≤ x ≤ 0.20) exhibited ferromagnetic (FM) natures. At 10K, all of the synthesized NPs displayed FM behavior. An enhancement in the Mr, Ms, Hc, and n B was detected at lower Nd 3+ and Ce 3+ concentrations (x ≤ 0.10). The SQR values at RT were smaller than 0.5, indicating a single domain nature with uniaxial anisotropy in all of the produced ferrites. However, the SQR values were in a range of 0.687–0.769 at 10K, suggesting a multi-magnetic domain at low temperatures. This study also examined the impact of Nd 3+ - and Ce 3+ -doped cobalt ferrite nanoparticles on human colon cancer cells (HCT-116) to examine their anti-cancer properties using MTT and morphometric assays. After 48 h of treatment with an optimal dose of Nd 3+ and Ce 3+, the doped cobalt ferrite nanoparticles demonstrated significant apoptotic effects by decreasing cancer cell viability in a dose-dependent manner. These results could lead to the use of NPs as a drug-screening/potential therapeutic strategy targeting human colorectal cancer. Graphical abstract: CoNdx Cex Fe2-2x O4 nanoparticles were prepared sonochemically. Structural, magnetic and apoptotic properties were investigated.Image 1 Highlights: CoNdx Cex Fe2-2x O4 (x = 0.00, 0.05, 0.10 and0.20) NPs were fabricated by sonochemical method. It showed superparamagnetic (SPM) nature for x = 0.00 sample at RT. However, the other products (0.03 ≤ x ≤ 0.20) exhibit ferromagnetic (FM) nature. Nd 3+ and Ce 3+ co-substitutions affect considerably the magnetizations data. The impact of Nd 3+ and Ce 3+ doped cobalt ferrite nanoparticles on human colon cancer cells (HCT-116) is profound apoptotic effect by decreasing in cancer cell viability.